Into the Maelstrom: Music, Improvisation and the Dream of Freedom, before 1970 - Toop, David (New York London Bloomsbury, 2021)
In this first installment of acclaimed music writer David Toop's interdisciplinary and sweeping overview of free improvisation, Into the Maelstrom: Music, Improvisation and the Dream of Freedom: Before 1970 introduces the philosophy and practice of improvisation (both musical and otherwise) within the historical context of the post-World War II era. Neither strictly chronological, or exclusively a history, Into the Maelstrom investigates a wide range of improvisational tendencies: from surrealist automatism to stream-of-consciousness in literature and vocalization; from the free music of Percy Grainger to the free improvising groups emerging out of the early 1960s (Group Ongaku, Nuova Consonanza, MEV, AMM, the Spontaneous Music Ensemble); and from free jazz to the strands of free improvisation that sought to distance itself from jazz. In exploring the diverse ways in which spontaneity became a core value in the early twentieth century as well as free improvisation's connection to both 1960s rock (The Beatles, Cream, Pink Floyd) and the era of post-Cagean indeterminacy in composition, Toop provides a definitive and all-encompassing exploration of free improvisation up to 1970, ending with the late 1960s international developments of free music from Roscoe Mitchell in Chicago, Peter Brötzmann in Berlin and Han Bennink and Misha Mengelberg in Amsterdam.
Keywords: 20th Century (1901-2000); Cultural history; Music history; Improvisation; Music philosophy and esthetics